Socio-Psychological Aspects of Formation of Nutritional Behavior in Teenage - Kulchytska, Anna; Fedotova, Tetiana (Psychological Prospects Journal, 2019)
The article theoretically observes the problem of nutritional behavior of the personality (L. Ponomareva, R. Komer, O. Samoylov, T. Yablonskaya, etc.), which determines not only tastes, inclinations, values, personality settings, but also cultural, ethnic and religious affiliation, reproduces the psychological portrait of the individual, carries hidden information about his individual characteristics. The risk of violations of the person’s eating behavior is related to low social adaptation, difficulties in establishing interpersonal relationships, family situation, etc. (A. Zanozin, V. Sutchuk, V. Shebanova, etc.). It has been empirically determined that adolescents in the risk group are characterized by emotional and external behavior in eating. In their attitude to themselves, there is a degree a certain of closed level of self-leadership, internal conflict and a tendency to self-accusation. Schoolchildren in this group define their parents’ attitude toward them as dictatorial, hostile and inconsistently destructive. Consequently, it is difficult for adolescents to handle emotions without having to resort to food, and to be restrained from food; as it performs a psychotherapeutic function for them. They are inclined to «eat» their problems and thus compensate their shortcomings, as evidenced by the correlation links of emotional behavior in eating with hostile attitude of parents and closed attitude to themselves; external eating behavior with dictatorial attitude and self-accusation. The nutritional behavior of adolescents in the norm group is characterized by the ability to limit themselves in food, the desire to eat rationally. They are characterized by self-confidence, self-acceptance, expectation of a positive attitude on the part of others and awareness of self-value. Teens have defined the attitude of their parents as autonomously-detached and positive-harmonious. So on the one hand, there is trust and positive interest of parents in their child, their full psychological acceptance; on the other hand, there is no tendency for protection and demarcation from the problems of children, evaluation of them as adults. There are correlation bonds of restrictive eating behavior with autonomously-detachment and positively-harmonious attitude of parents, and with self-confidence are established; external eating behavior with self-perception.